Impact of Conservation and Development on the Vicinity of Nanda Devi National Park in the North India - Pratiba Naitthani; Sunil Kainthola (Revue de Géographie Alpine)
Both the hydropower and the conservation sectors are concentrating their focus on the Himalayas, which have high hydropower potential and rich bio-cultural diversity. The aim of this present study, carried out in villages adjacent to the Nanda Devi National Park in the Himalayan state of Uttarakhand in India, is to understand the linkages between conservation- and development-induced displacement and the process of designing compensation packages for the local community. The study also examines the various gender-specific impacts of displacement, and the results suggest significant gender-specific differences regarding the impact of displacement in critical respects. The findings further indicate that, despite an early recommendation to do so, no impact assessment study had been conducted prior to the notification of the area as a national park. Furthermore, there appears to be no systematic linkage between the compensatory schemes and the grievances of the impacted communities.